Preparing Clinical Nurses for Nursing Research: Evaluation of Training Procedures in a Palliative Care Pilot Study. Issue 1 (January 2018) - Pittroff, Gail Elaine; Hendricks-Ferguson, Verna L.
Abstract : ABSTRACT: The importance of academic nurse researchers partnering with clinical nurses for clinical research has been well articulated. A 4-hour training program designed to equip staff nurses to become fully engaged researchers in a palliative care end of life communication-focused research study resulted in enriched human caring skills and professional growth. Results indicate that the training (didactic lecture, group reflection, role-playing) was adequate to prepare the nurses to deliver the study protocol. Relevance for primary investigators, nurses, clinical institutions, those interested in partnered research, and professional growth are discussed.